2017
DOI: 10.1590/2317-6431-2016-1746
|View full text |Cite
|
Sign up to set email alerts
|

Limiar diferencial de mascaramento: valores de referência em adultos

Abstract: RESUMO Introdução O Limiar Diferencial de Mascaramento é um teste comportamental que avalia o mecanismo de interação binaural do processamento auditivo. Objetivo Descrever o Limiar Diferencial de Mascaramento em adultos, a fim de contribuir para o estabelecimento de valores de referência para o teste. Métodos Foram avaliadas 109 mulheres sem queixas auditivas e com audiometria normal. Foi utilizada a versão do Limiar Diferencial de Mascaramento da Auditec of Saint Louis, que consiste na apresentação de 33 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
2
4
0
3
Order By: Relevance
“…In this study, an average threshold value of 10.83 dB was obtained, which is very similar to what we found in our G3, with an average threshold value of 11 dB. 28 Regarding the values found in children, in G1 of our study, in which girls aged 9 to 13 years old were evaluated, we found the average threshold value at 9.2 dB. This result corroborates a very recent study that evaluated the MLD in the age group from 7 to 12 years old, in which the threshold of 9.3 dB was suggested as a cutoff criterion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, an average threshold value of 10.83 dB was obtained, which is very similar to what we found in our G3, with an average threshold value of 11 dB. 28 Regarding the values found in children, in G1 of our study, in which girls aged 9 to 13 years old were evaluated, we found the average threshold value at 9.2 dB. This result corroborates a very recent study that evaluated the MLD in the age group from 7 to 12 years old, in which the threshold of 9.3 dB was suggested as a cutoff criterion.…”
Section: Discussionsupporting
confidence: 91%
“…The test was considered altered when the threshold was < 10 dB. 28 The auditory skill assessed was binaural interaction. 15 We chose to study the central auditory skills in the overall sample and then in the sample stratified by age to verify if there was a difference in performance in the behavioral tests in each group.…”
Section: Methodsmentioning
confidence: 99%
“…The normative values suggested by Pereira et al, 10 Auditec, 11 and Mendes et al, 12 were considered in the auditory processing exam. Only individuals with normal audiological assessment and auditory processing assessment were selected to participate in the second stage of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The normality standard considered for each test was the one proposed in the literature. [23][24][25]27…”
Section: Assessment Of Central Auditory Processingmentioning
confidence: 99%